Does Love Really Make Mothers Blind? A Large Transcontinental Study on Mothers' Awareness About Their Children's Weight. Issue 7 (22nd June 2018) - Gregori, Dario; Hochdorn, Alexander; Azzolina, Danila; Berchialla, Paola; Lorenzoni, Giulia; ,
Abstract : Objective: The aim of this study was to assess maternal misperception rates (perception as normal or underweight of a child with overweight or obesity) and their role in affecting the chance of implementing actions to change children's weight. Methods: Obesogeneicity of Gadgets Marketed with Snacks (OBEY‐AD) is an international study investigating factors promoting childhood overweight and obesity in 10 countries, in which 2, 720 child‐mother dyads have been enrolled. Mothers' perception of their children's weight was assessed using a projective test. Children's weight status was measured according to the anthropometric standards established by the World Health Organization. Results: Mothers classified 89% of children with overweight and 52% of children with obesity as normal weight. The odds ratio of mothers' misperception was significantly higher for higher parental BMI, higher children's International Brand Awareness Inventory score, and high family socioeconomic status. Children with overweight and/or obesity who were perceived as normal weight by their mothers were less likely to be referred to specific health care services. Conclusions: Most children with overweight and/or obesity were perceived as normal weight by their mothers. Such lack of concern regarding a severe disease might interfere with the effectiveness of prevention programs. Considering the contextual factors that frame the etiological causes of a disease may help in finding effective and enduring solutions to target childhood obesity.